Differential proteome–metabolome profiling of YCA1-knock-out and wild type cells reveals novel metabolic pathways and cellular processes dependent on the yeast metacaspase1. Issue 6 (19th June 2015) - Ždralević, Maša; Longo, Valentina; Guaragnella, Nicoletta; Giannattasio, Sergio; Timperio, Anna Maria; Zolla, Lello
<x xml:space="preserve">Abstract</x> A combined proteomic and metabolomic approach revealed new non-apoptotic roles of the metacaspase YCA1 gene in Saccharomyces cerevisiae, highlighting its involvement in the cell metabolism and stress response.